Analisis Kekerabatan Menggunakan Metode Fingerprint DNA pada Ikan Sepat (Ordo Anabantiformes) di Perairan Kecamatan Kualuh Leidong - Desi Ritonga; Zahratul Idami; Kartika Manulu (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Gourami is a type of freshwater fish that is widely distributed in Indonesia, including in the waters of Kualuh Leidong District, North Sumatra. However, the kinship relationship between gourami species in the region has not been widely studied. Therefore, this study aims to analyze the kinship relationship of several gourami species found in the waters of Kualuh Leidong using the DNA fingerprint method. This study uses a molecular characterization method with several stages, namely collecting fish samples, isolating and extracting DNA, amplifying DNA using Polymerase Chain Reaction (PCR) with several primers, electrophoresis, and analyzing data using NTSYS software. Sampling was carried out by collecting specimens from the waters of Kualuh Leidong, including four types of gouramis, namely Trichopodus trichopterus, Trichopodus pectoralis, and Helostoma temmincki. The electrophoresis results showed that the DNA of the gourami fish could be amplified with primers OPA 02, OPC 02, and UBC 456, but not amplified with primer OPA 20. The DNA banding pattern obtained consisted of polymorphic and monomorphic bands with varying locus sizes. Jaccard coefficient analysis showed a high level of kinship (>70%), with the species Trichopodus pectoralis having a similarity of 0.78, Trichopodus trichopterus 0.76, and Helostoma temmincki 0.71. The results of this study can be used as a basis for the conservation and management of gourami fish resources in the waters of North Sumatera.